Antimicrobial Resistance Profile of Foodborne Salmonella spp. and E. coli Isolates from Rodents and Shrews in Morogoro Municipality, Tanzania - Marie Chantal Uwanyirigira; Elias Nelly Bapfakurera; Elisa Mwega; Sharadhuli Kimera; Abdul A.S. Katakweba (Journal of Applied Veterinary Science And Technology, 2024)
Background: Antimicrobial resistance (AMR) is a pressing global public health issue that affects both human and animal health. Small mammals, such as rodents and shrews, represent a significant reservoir of zoonotic infections. However, there is limited documented research specifically addressing Escherichia coli and Salmonella spp. resistant strains from small mammals. Purpose: This study was conducted to examin the occurrence of AMR E. coli and Salmonella spp. and their associated resistance genes in rodents and shrews. Methods: A total of 148 fecal samples from rodents and shrews were examined for E. coli and Salmonella spp. using culture methods and biochemical tests. Fifty isolates were subjected to antibiotic susceptibility testing using the disk diffusion method on Muller-Hinton agar. Genotypic analysis by PCR was used to confirm the bacterial strains and their resistance pattern genes. Results: Two bacteria were confirmed in 57 (38.5%) of the fecal samples. Specifically, E. coli and Salmonella spp. were identified in 54 (36.5%) and 3 (2%) fecal samples, respectively. Antimicrobial susceptibility testing revealed significant resistance in Rattus rattus. Molecular analysis confirmed that Salmonella spp.  carry a larger proportion of resistance genes than E. coli. Specific resistance genes, including Sul1 and Sul2, were identified, constituting 15.4% of the total resistance genes. The prevalence of β-lactamase genes was remarkable, with a higher occurrence in Salmonella spp. Conclusion: In terms of human health, the implications of rodents and shrews serving as carriers and transmitters of various pathogens were highlighted. Given the possibility of unexpected zoonoses arising from the bacteria found in this study, these findings contribute to the understanding AMR in the context of bacterial infections in animals and humans.